2021
DOI: 10.3390/nu13092921
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Monosodium Glutamate Suppresses Chemotherapy-Induced Downregulation of the T1R3 Taste Receptor Subunit in Head and Neck Cancer Patients

Abstract: (Background) We investigated the effect of dietary supplementation with monosodium glutamate (MSG) on chemotherapy-induced downregulation of the T1R3 taste receptor subunit expression in the tongue of patients with advanced head and neck cancer. (Methods) Patients undergoing two rounds of chemoradiotherapy were randomly allocated to a control or intervention group (dietary supplementation with MSG at 2.7 g/day during the second round of chemotherapy). The relative expression of T1R3, a subunit of both umami an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Furikake has proven valuable in nutrition research. For instance, a furikake variant involving monosodium salt of L-glutamate (MSG) was used in a clinical trial aimed at improving taste abnormalities in healthy young individuals [12] and in cancer patients with taste abnormalities caused by anti-cancer drugs [13]. In Japanese nursing homes, residents often gather around a table to share meals.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Furikake has proven valuable in nutrition research. For instance, a furikake variant involving monosodium salt of L-glutamate (MSG) was used in a clinical trial aimed at improving taste abnormalities in healthy young individuals [12] and in cancer patients with taste abnormalities caused by anti-cancer drugs [13]. In Japanese nursing homes, residents often gather around a table to share meals.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Treatment with monosodium glutamate has been recently shown to increase the expression of the taste receptor subunit T1R3 and increase energy intake in patients with advanced head and neck cancer. 64 …”
Section: Management Of Cancer-related Anorexiamentioning
confidence: 99%
“…Treatment with monosodium glutamate has been recently shown to increase the expression of the taste receptor subunit T1R3 and increase energy intake in patients with advanced head and neck cancer. 64 Oral mucositis is a common side effect of both chemotherapy and radiotherapy. 65 Glutamine has been studied as a treatment for chemotherapy-and radiotherapy-induced oral mucositis: a recent systematic review of several clinical trials showed that patients treated with glutamine had a significantly reduced incidence of severe (grade 3 or 4) oral mucositis.…”
Section: Treatment Of Associated Symptomsmentioning
confidence: 99%
“…We previously reported that lingual taste receptor gene expression decreases during chemotherapy in patients with head and neck cancer (10). Lingual taste receptors are stimulated by the taste of substances such as monosodium glutamate (MSG), thereby increasing taste receptor gene expression (17,18). However, we recently reported that the taste receptors of subjects with diabetes are expressed differently from those of the general population, suggesting overexpression due to overeating in the patients (19).…”
Section: Introductionmentioning
confidence: 99%